NAD(P)H: Quinone oxidoreductase 1 overexpression in hepatocellular carcinoma potentiates apoptosis evasion through regulating stabilization of X-linked inhibitor of apoptosis protein - Li, Wan-Yu; Zhou, Hong-Zhong; Chen, Yao; Cai, Xue-Fei; Tang, Hua; Ren, Ji-Hua; Wai Wong, Vincent Kam; Kwan Law, Betty Yuen; Chen, Yong; Cheng, Sheng-Tao; Yu, Hai-Bo; Cai, Hao-Yang; et al. (Cancer letters, 2019)
NAD(P)H: quinone oxidoreductase 1 (NQO1) is an antioxidant enzyme which is associated with poor prognosis in human breast, colon, lung and liver cancers. However, the molecular mechanisms underlying the pro-tumorigenic function of NQO1 remains unclear. This study investigated the function of NQO1 in the context of hepatocellular carcinoma (HCC) development. We found that NQO1 was frequently up-regulated in human liver cancer, and its high expression level was correlated with the tumor stage and low survival rate of HCC patients. Loss-of-function of NQO1 inhibited growth in HCC cells with increased apoptosis in vitro, and suppressed orthotopic tumorigenicity in vivo. Mechanistically, high level of NQO1 in HCC cells enhanced protein stability of X-linked inhibitor of apoptosis protein (XIAP) by increasing its phosphorylation at Ser 87. Reintroduction of wile type XIAP and the phospho-mimic mutants XIAPS87D significantly reversed NQO1 knock-down/out induced growth inhibition and apoptosis. In mouse model with orthotopically implanted hepatocarcinoma, NQO1 suppression and NQO1 inhibitor suppressed tumor growth and induced apoptosis. NQO1 plays an important role in sustaining HCC cell proliferation and may thus act as a potential therapeutic target in HCC treatment. •NQO1 was frequently up-regulated in human liver cancer, and its high expression level was correlated with poor prognosis.•Loss-of-function of NQO1 induced cellular apoptosis by decreasing XIAP in vitro and in vivo.•Mechanistically, NQO1 enhanced protein stability of XIAP by increasing its phosphorylation at Ser 87.